2022
DOI: 10.1190/geo2021-0524.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of temperature change effect on distributed acoustic sensing continuous measurements

Abstract: Distributed fibre-optic sensing is being actively used in various exploration and monitoring applications. Distributed temperature sensing (DTS) is used for measurements and monitoring of the temperature and Distributed acoustic sensing (DAS) for recording of the seismic wavefield. However, DAS measurements are also sensitive to temperature changes. Understanding how exactly DAS measurements are affected by temperature variations is important in order to remove this effect from DAS seismic data. This can be pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Note that CO 2 injection causes not only changes in the reservoir properties but also changes of the borehole environment such as temperature, which can also affect the DAS response [ 31 ]. However, these changes are spread over a large depth range, while changes in the DAS response in our study are limited to the reservoir interval.…”
Section: Co 2 Plume Detection Resultsmentioning
confidence: 99%
“…Note that CO 2 injection causes not only changes in the reservoir properties but also changes of the borehole environment such as temperature, which can also affect the DAS response [ 31 ]. However, these changes are spread over a large depth range, while changes in the DAS response in our study are limited to the reservoir interval.…”
Section: Co 2 Plume Detection Resultsmentioning
confidence: 99%
“…The uncertainty in these parameters is challenging to quantify, since no calibration has been performed in situ, but a factor of two deviation in the strain‐to‐temperature relation is conceivable. Cable construction and burial can only thermally insulate the fiber, so the conversion used here should otherwise represent the minimum value of relative temperature (Sidenko et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, only in recent years there have been publications demonstrating the diverse geophysical applications of low frequency DAS (LF-DAS) signals that are dominated by temperature [34,35,36,37,38,39]. In particular, Ide et al, 2021 [37] found distinctive patterns with several-hours periodicity on underwater LF-DAS data from a cable offshore Japan.…”
Section: Das Thermometrymentioning
confidence: 99%
“…The current lack of knowledge about the exact transfer function between the optical fiber response and the input ambient temperature hampers the exact estimation of the latter. Although this transfer function is reportedly linear [37,39], it is generally expected to be a function of the composition and structure of each cable [35,95] and its coupling and thermal insulation by the host medium, from which detailed information is often lacking. This limitation, however, could be overcome through unique, temporary or regular temperature calibrations at single or multiple cable locations with dedicated temperature sensors and/or with auxiliary DTS/DSTS systems [96], depending on the required precision and possible logistics.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation